Head of the Department of Economics, Security and Innovation of the Enterprise of the Lesia Ukrainka Eastern European National University (Economic journal of Lesya Ukrainka Volyn National University, 2018)
Assessment of readiness of machine-building enterprises for introduction of social responsibility of business in Ukraine.The index of industrial production in machine building of Ukraine, the share of sold production of mechanical engineering in industrial products (goods, services) without VAT and excises, the share of profitable enterprises of machine building in Ukraine. The companies are grouped by type of economic activity, which comprise social reports in Ukraine.The purpose of the work is to assess the readiness of machine-building enterprises to introduce social responsibility of business in Ukraine.Machine building is one of the types of economic activity that determines the competitiveness of Ukraine's economy and determines its place in the world. Today the state of the machine-building industry of Ukraine does not correspond to the signs of sustainable development. It is characterized by physical and moral depreciated assets, a low percentage of innovative enterprises, low level of implementation of low-cost and resource-saving processes, low level of investments, difficult political and economic situation in the country, high energy costs, weak interaction between production and research and development.The share of the sold products of machine-building in 2014 is 7,9 %, in 2015, 6,9 %, – in 2016 – 6,6 %. Of these, 54,1 % of sold products are shipped abroad in 2014, 55,5 % in 2015, 47,4 % in 2016. Thus, there is a decrease in the share of sold products of machine building outside the country.In 2014–2016, the share of profitable enterprises in industry increased from 63,3 % – to 72,8 %, but in 2015 their share was 72,9 %, and in 2016 it was 72,8%, which testifies to tendency to decrease. In machine building, the share of profitable enterprises for 2014–2016 is higher in comparison with industry.Machine building occupies 16,96 % in 2014 in industry, in 2015, 16,86 %, in 2016, 17,09 %. Thus, the state of the domestic machine-building enterprises, according to the results of their activities and general tendencies, has been considered satisfactory, which will promote the introduction of social responsibility of enterprises.Machine-building enterprises in Ukraine are just beginning to implement the principles of social responsibility of business, the environment of their functioning is ready for their distribution. However, the highest level of readiness for corporate social responsibility is observed in the food and agrarian industries, communication companies, and services.
Keywords: social responsibility, enterprise, business, evaluation, index of industrial production, social report.